2019
DOI: 10.1177/1471301219831525
|View full text |Cite
|
Sign up to set email alerts
|

Telling a ‘good or white lie’: The views of people living with dementia and their carers

Abstract: Objective: A common symptom of cognitive decline in people living with dementia, or people with memory problems, the cause of which has not yet been diagnosed, is the person repeatedly asking for loved ones who are deceased or making statements that are incorrect. Carers are then faced with a dilemma, do they avoid and distract or 'correct' the person and tell the 'truth', or tell a lie. This paper explores the concept of lying from the perspective of people living with dementia in the community and their info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Fear of regulatory noncompliance might lead staff to attempt too many behavioral interventions, prolonging a resident’s pain or distress or putting staff or other residents in harm’s way ( 57 ). Participants shared that doing what is best for the resident should drive decision-making, even if what is perceived as “best” includes elements of deception (eg, white lies) ( 58 ). However, resource constraints and organizational obstacles present significant barriers to the person-centered approach that is often required, and recommended as best practice ( 9 , 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fear of regulatory noncompliance might lead staff to attempt too many behavioral interventions, prolonging a resident’s pain or distress or putting staff or other residents in harm’s way ( 57 ). Participants shared that doing what is best for the resident should drive decision-making, even if what is perceived as “best” includes elements of deception (eg, white lies) ( 58 ). However, resource constraints and organizational obstacles present significant barriers to the person-centered approach that is often required, and recommended as best practice ( 9 , 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of therapeutic untruths has raised a number of complex ethical issues and there are conflicting views about their appropriateness and acceptability. On the one hand, therapeutic untruths are seen as unprofessional, immoral, a fundamental betrayal of trust, or a form of abuse by those who oppose their use, 5 , 6 although people with dementia themselves condone their use under certain circumstances, that together constitute an action that is in the best interests of the person. 6 , 7 On the other hand, therapeutic untruths are seen as a means of communication with people who have memory loss, a decline in functional ability and who may create their own reality, 8 or as a strategy to alleviate anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, therapeutic untruths are seen as unprofessional, immoral, a fundamental betrayal of trust, or a form of abuse by those who oppose their use, 5 , 6 although people with dementia themselves condone their use under certain circumstances, that together constitute an action that is in the best interests of the person. 6 , 7 On the other hand, therapeutic untruths are seen as a means of communication with people who have memory loss, a decline in functional ability and who may create their own reality, 8 or as a strategy to alleviate anxiety. 9 Indeed, it has been suggested that the ethical principal of beneficence and preventing harm to others may well be interpreted in some situations as requiring the professional to use therapeutic untruths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Casey et al's study also highlighted motivation as a key element of telling a 'good lie'. 3 As new emerging research contributes to the debate about lie telling, it may be that nurses caring for people with dementia should no longer ask themselves 'should I lie?' but rather 'if I must lie, how can I be genuine in my interaction, and what is my motivation?…”
mentioning
confidence: 99%